2022
DOI: 10.31234/osf.io/gndcu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensing fear: Fast-and-precise threat evaluation in human sensory cortex

Abstract: Animal models of threat processing have evolved beyond the amygdala to incorporate a distributed neural network. In human research, evidence has intensified in recent years to challenge the canonical threat circuitry centered on the amygdala, urging revision of threat conceptualization. A strong surge of research into threat processing in the sensory cortex in the past decade has generated particularly useful insights to inform the re-conceptualization. Here, synthesizing findings from both animal and human re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Overall, we observed that the pandemic group showed a reduction over time of brain activations associated with FALT across different phases and brain regions. While we acknowledge that the brain regions identified in our current study may not conventionally align with fear learning tasks, it is important to note that a number of studies have highlighted instances of modified context and sensory processing within fear-related fMRI tasks [see (11,43) for reviews]. We speculated that social isolation and physical confinement secondary to quarantine measures during the pandemic may have driven these FALT-related brain activation alterations.…”
Section: Discussionmentioning
confidence: 80%
“…Overall, we observed that the pandemic group showed a reduction over time of brain activations associated with FALT across different phases and brain regions. While we acknowledge that the brain regions identified in our current study may not conventionally align with fear learning tasks, it is important to note that a number of studies have highlighted instances of modified context and sensory processing within fear-related fMRI tasks [see (11,43) for reviews]. We speculated that social isolation and physical confinement secondary to quarantine measures during the pandemic may have driven these FALT-related brain activation alterations.…”
Section: Discussionmentioning
confidence: 80%